Can Dogs be Racist? The Colonial Legacies of Racialized Dogs in Kenya and Zambia. (12th February 2020) - Doble, Josh
Abstract: Can dogs be racist? Posing this question may seem odd and at worst, unhelpfully provocative at a time when the discourse of 'colour-blindness' is so pervasive. Yet the idea of 'racist dogs' remains salient within the post-settler societies of eastern and southern Africa, where dogs have been an integral if overlooked tool of colonial practices of racialization. This article traces the colonial demarcation of 'native dogs' – juxtaposed to white settlers' 'pet' dogs – to understand how racial categories were imposed on domesticated animals, and how these racialized animals were then colonized through rabies legislation. Although the formal racialization of dogs ended with the dawn of political decolonization in the early 1960s, dogs continued to be co-opted for postcolonial racial discourse. Dogs were in a prominent position in postcolonial society due to their prevalence in the security arrangements of white homes as well as in the security forces of white supremacist Rhodesia and apartheid South Africa. The intensity of the relationship between white minorities, their canine pets and the surrounding African population points toward the uncomfortable conclusion that in the heightened racial environments of decolonizing settler Africa, dogs could be made to be racist.